Behavioral, neurotransmitter and transcriptomic analyses in male and female Fmr1 KO mice - McCarthy, Deirdre M.; Vied, Cynthia; Trupiano, Mia X.; Canekeratne, Angeli J.; Wang, Yuan; Schatschneider, Christopher; Bhide, Pradeep G. (Frontiers in Behavioral Neuroscience, 2024)
Fragile X Syndrome is an inherited X-linked disorder associated with intellectual disabilities that begin in childhood and last a lifetime. The symptoms overlap with autism spectrum disorder, and the syndrome predominantly affects males. Consequently, FXS research tends to favor analysis of social behaviors in males, leaving a gap in our understanding of other behavioral traits, especially in females. Here we used a mouse model of FXS to analyze developmental, behavioral, neurochemical, and transcriptomic profiles in males and females. Our behavioral assays demonstrated locomotor hyperactivity, motor impulsivity, increased "approach" behavior in an approach-avoidance assay, and deficits in nest building behavior. Analysis of brain neurotransmitter content revealed deficits in striatal GABA, glutamate, and serotonin content. RNA sequencing of the ventral striatum unveiled expression changes associated with neurotransmission as well as motivation and substance use pathways. Sex differences were identified in nest building behavior, striatal neurotransmitter content, and ventral striatal gene expression. In summary, our study identified sex differences in specific behavioral, neurotransmitter, and gene expression phenotypes and gene set enrichment analysis identified significant enrichment of pathways associated with motivation and drug reward.